2015
DOI: 10.1007/s11904-015-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Alcohol Use and Related Disorders on the HIV Continuum of Care: a Systematic Review

Abstract: Alcohol use is highly prevalent globally with numerous negative consequences to human health, including HIV progression, in people living with HIV (PLH). The HIV continuum of care, or treatment cascade, represents a sequence of targets for intervention that can result in viral suppression, which ultimately benefits individuals and society. The extent to which alcohol impacts each step in the cascade, however, has not been systematically examined. International targets for HIV treatment as prevention aim for 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
137
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 95 publications
5
137
3
8
Order By: Relevance
“…A systematic review found that alcohol users were more likely to have missed at least one or more cascades of continuum of care such as attending treatment services, ART compliance, routine investigation of viral loads, and CD4 count [20]. Additionally, alcohol users also engage in substance use as a coping mechanism for reducing stress related to HIV, which further deteriorates their health [21].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found that alcohol users were more likely to have missed at least one or more cascades of continuum of care such as attending treatment services, ART compliance, routine investigation of viral loads, and CD4 count [20]. Additionally, alcohol users also engage in substance use as a coping mechanism for reducing stress related to HIV, which further deteriorates their health [21].…”
Section: Introductionmentioning
confidence: 99%
“…Esto suscribe en nuestro entorno asistencial y cultural lo señalado amplia y consistentemente en la literatura previa en otros contextos (Azar et al, 2010;Vagenas et al, 2015;Hendershot et al, 2009). En el presente estudio, además, la asociación entre el consumo de alcohol y la falta de adherencia se mantiene tras el ajuste por otros consumos por lo que, en la muestra estudiada, el alcohol deteriora la adherencia de manera independiente al uso o no de otras sustancias.…”
Section: Discussionunclassified
“…En los últimos años, numerosos autores han prestado especial atención a las repercusiones del consumo de alcohol sobre el cumplimiento terapéutico (Vagenas et al, 2015). Diferentes revisiones sistemáticas sustentan de manera consistente la relación entre ambos factores (Azar et al, 2010;Vagenas et al, 2015;Hendershot, Stoner, Pantalone y Simoni, 2009).…”
unclassified
See 1 more Smart Citation
“…Among persons living with HIV (PLH), there is consistent evidence linking hazardous drinking to lower adherence to antiretroviral therapy, higher rates of condomless sex, and greater number of sexual partners (Azar, Springer, Meyer, & Altice, 2010; Kalichman et al, 2014; Shuper, Joharchi, Irving, & Rehm, 2009; Vagenas et al, 2015), and an increased risk of HIV progression and transmission (Baliunas, Rehm, Irving, & Shuper, 2009; Shuper et al, 2010). Impulsivity and sensation seeking have been linked to hazardous drinking, increased sexual risk behaviors, and lower treatment adherence (Hendershot, Stoner, George, & Norris, 2007; Shin, Hong, & Jeon, 2012).…”
Section: Introductionmentioning
confidence: 99%